Studies on the pre-treatment of palm oil mill effluent - Wong, Pin Sing (Curtin University, 2012)
The feasibility of using hydrochloric acid (HCl), heat, dilution and magnetic stirring for the pre-treatment of palm oil mill Effluent (POME) before the primary anaerobic treatment was investigated in this study. The theoretical background of oily water emulsion which is the characteristic of POME was reviewed. A range of experiments was performed on samples made up of different combinations of the three major components of POME namely, palm oil, solid from decanter and water. The results suggest that the development of a pre-treatment system to remove the 0.5- 1.2% residue oil and 3-4% solid matter from the fresh POME is feasible thus it could improve the efficiency of further downstream POME treatment.Experiments were conducted to examine the rate of oil flotation from the mixtures of different ratios of palm oil and water treated with different concentrations of HCl, and temperatures and magnetic stirring. Similarly, a series of experiments were performed to determine the rate of solid settlement from palm oil-solid mixture, solid-water mixture and palm oil-solid-water mixture of different ratios treated with different concentrations of HCl and different temperatures. The data obtained from the experiments were used to determine the optimum dosage of HCl used and the temperature required for best oil recovery and solid settlement.From the kinetic studies, the models of the kinetic rate of palm oil flotation and solid settlement were derived. A macro kinetic modeling was adapted to the oil flotation while a power model was used for solid settling. The results showed that treatment with 0.5% HCl was sufficient to increase the rate of oil flotation significantly in Palm oil-water mixture. However, the effect was dependent on the oil-water ratio. An increase in temperature gave higher rate of oil flotation but not as great as that of HCl treatment. Dilution was found to be the two other factors that affected the rate of flotation. The solid settling rates in all tested samples were not significantly affected when they were treated with HCl. The rate of solid settlement was found to be temperature dependent. The optimum temperature for the rate of solid sedimentation was found to be in the region of 800C. Similar positive effect was also observed for a more diluted sample of Solid-Palm oil-Water mixture.